ChemInform Abstract: Catalyst‐Free Chemo‐/Regio‐/Stereoselective Amination of Alk‐3‐ynones. Synthesis of 1, 5‐Benzodiazepines and 3‐Amino‐2‐alkenones. Issue 31 (5th August 2014) - Solan, Agnes; Nisanci, Bilal; Belcher, Miranda; Young, Jonathon; Schaefer, Christian; Wheeler, Kraig A.; Toeroek, Bela; Dembinski, Roman
Abstract The microwave‐assisted cyclocondensation of alkynones (I) with o‐phenylenediamines (II) leads to desired 1, 5‐benzodiazepines (III) in good yields.